2014
DOI: 10.1093/eurpub/cku203
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-free schools as a core component of youth tobacco prevention programs: a secondary analysis of data from 43 countries

Abstract: Comprehensive tobacco prevention programs that include well-enforced smoke-free school policies may help reduce youth smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…However, not all teachers are totally prepared, as the fight against smoking and educational programs have not represented a public health priority so far [30], as reflected by our study [43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…However, not all teachers are totally prepared, as the fight against smoking and educational programs have not represented a public health priority so far [30], as reflected by our study [43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…These largely positive findings contrast with an analysis of 43 countries (including non-LLMICs) that found no independent association between smoking behaviour and exposure to school-based group counselling. 68 …”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that a multidisciplinary approach involving the media, community and legislative authorities is needed in addition to health-promoting initiatives at the school level. Moreover, a study encompassing GYTS data from 43 countries conveyed that an increased awareness about the harm of tobacco among students was associated with the presence of tobacco prevention courses in their respective schools 27 . In addition, a review by Backinger et al 28 revealed that school curricula alone are ineffective in preventing youth smoking, unless coupled with other methods such as smoke-free policies 28 .…”
Section: Resultsmentioning
confidence: 99%